1997
DOI: 10.1002/(sici)1097-4547(19971215)50:6<979::aid-jnr8>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Rapid impact of ?-amyloid on Paxillin in a neural cell line

Abstract: Beta-amyloid1-42 (Abeta) is a naturally occuring peptide whose accumulation in the brain is putatively coupled to Alzheimer's disease pathogenesis. Deleterious effects of Abeta on neurons have been linked to the inappropriate activation of signaling pathways within the cell (reviewed in Yankner, 1996), including tyrosine phosphorylation of focal adhesion kinase (FAK) (Zhang et al., 1994, 1996a,b). Here we have investigated the effects of Abeta on paxillin in a neural cell line. Paxillin, a substrate for FAK, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 75 publications
1
17
0
Order By: Relevance
“…1C,D). This result is consistent with previous reports showing the activation of Tyr kinase activity and increased paxillin Tyr phosphorylation in neuronal cells treated with fibrillar A␤ (Berg et al, 1997;Williamson et al, 2002). Paxillin translocation to the cytoskeleton was assessed by Western blot of whole-cell homogenates and cytoskeletal preparations.…”
Section: Fibrillar A␤-induced Neuronal Dystrophy Paxillin Tyr Phosphsupporting
confidence: 92%
See 1 more Smart Citation
“…1C,D). This result is consistent with previous reports showing the activation of Tyr kinase activity and increased paxillin Tyr phosphorylation in neuronal cells treated with fibrillar A␤ (Berg et al, 1997;Williamson et al, 2002). Paxillin translocation to the cytoskeleton was assessed by Western blot of whole-cell homogenates and cytoskeletal preparations.…”
Section: Fibrillar A␤-induced Neuronal Dystrophy Paxillin Tyr Phosphsupporting
confidence: 92%
“…In this regard, fibrillar A␤ could promote dystrophy by aberrantly activating signal transduction cascades leading to cytoskeletal changes (Saitoh et al, 1993). A␤ binds to integrins (Kowalska and Badellino, 1994;Sabo et al, 1995;Goodwin et al, 1997) and activates the focal adhesion (FA) proteins paxillin and focal adhesion kinase (FAK), which are downstream of integrin receptors, suggesting that FA signaling cascades might be involved in A␤-induced neuronal dystrophy, cell death, or both (Zhang et al, 1994(Zhang et al, , 1996Berg et al, 1997;Williamson et al, 2002). To address the role of FA signaling in A␤-induced neuronal dystrophy, we analyzed the expression and activity of FA proteins in the AD brain and in cultured neurons exposed to fibrillar A␤.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in nonneuronal cells have shown that both Ca 2ϩ and ROS are relevant to signaling via Src family protein tyrosine kinases (59)(60)(61). In neuronal cells, toxicity of traditional A␤ preparations also has been linked to transduction molecules associated with focal contact signaling (32,62,63), a cascade that includes Fyn (41). In B103 cells, ADDLs have been found to stimulate Fyn kinase Ϸ2-fold within 30 min (C.Z.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies suggest that activation of PI3K/Akt may protect against neuronal death induced by Aβ [e.g. 3,37], those same signaling pathways also have been reported to be activated by Aβ [e.g., 5,16,21,57]. Therefore, it is possible that ADDL binding to neuronal target receptors leads to aberrant activation of trophic signaling and to an incomplete set of downstream events that lead to tau hyperphosphorylation and neuronal dysfunction.…”
Section: Discussionmentioning
confidence: 99%